MODELING ANALYSIS AND EXPERIMENTAL RESEARCH OF THE MATERIAL REMOVAL RATE OF THE MONOCRYSTALLINE SILICON IN THE COURSE OF THE ELETRICAL DISCHARGE MACHINING - XIN Bin; LI ShuJuan; LU Xiong; DONG YongHeng; SHI WeiChao (Jixie qiangdu)
Based on the feasibility of the discharge machining of the semiconductor material,it analyze several major factors which influences the material removal rate,including the open circuit voltage,peak current,pulse width and pulse interval.Using central composite design experiments,it inspects the influence of the three factors peak current、pulse width and pulse interval to the material removal rate of the monocrystalline silicon in the course of the electrical discharge machining and establishes a response model of the material removal rate of the monocrystalline silicon in the course of the electrical discharge machining and makes analysis to the response surface. The result of the variance analysis indicate that the model has good fitting degree and adaptability. It uses satisfactory rate function（ DFA） to determine the optimum technology parameters of the monocrystalline silicon in the course of the electrical discharge When the value of the peak current is 18. 5 A,the value of the pulse width is 358. 62μs,the value of the pulse interval is 20μs and the degree of satisfaction is 0. 912,then the optimal value of the material removal rate is 76. 26 mm~3/min It has measured the average MRR of the P type monocrystalline silicon is 73. 86mm~3/min through repeated experiments many times on the electrical discharge shaping machine with the optimal processing parameters which are identified The average relative error of the model prediction results compare with experimental results under the optimum technological parameters is 3. 4%. The verification test indicates that this model can achieve the prediction of the material removal rate of the corresponding semiconductor material in the course of the discharge machining.